Community and enviroment - Gutkind, E. A. (New York, 1954)
The interaction between man, community, and environment is the eternal theme to which every generation has made its own contribution in its own language of form. It is a perennial transformation through which man and environment are passing; at times slower and with only slightly per ceptible vibrations of their mutual adaptation, at others with a quickening pace and a growing intensity. In our own time the tempo of this trans formation has accelerated, the scale widened, and the intensity increased at an unprecedented rate. It seems that nothing short of a far-reaching revolution in our way of thinking and of recasting our thoughts in a new mould of social aspirations is the demand of the hour. We are living in a period of one of the greatest human and social experiments, of one of the most fateful adventures in the history of mankind. New methods, new ideas, and new goals are needed which tax the imagination and the audacity of our own and future generations to the utmost.
Keywords: Community